2020
DOI: 10.1021/acs.jpcc.0c04185
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Ion Hybrid Capacitor with a Scaffold Electrode of Tin Sulfide and Tin Metal and Its Electrolyte Issue

Abstract: In an effort to exploit low-cost tin and sulfur as active materials in lithium-ion hybrid capacitors, we prepare a SnS−Sn/carbon nanotube (CNT) negative electrode through molten slag coating of acidified carbon nanotubes (CNTs) with a minimum level of surface oxidation. The capacity of this sulfur-containing electrode behaves more reversibly and less decaying in an ether-based electrolyte of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and LiNO 3 than the generalpurpose electrolyte of LiPF 6 . On the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…It was verified that the as-prepared SnS/C composite microspheres also displayed superior reversible capacities and excellent cycle performance, which have great potential for Na-ion batteries as anode materials. [154] Apart from that, SnS-based nanostructures containing 1D SnS nanomaterials in a capsulated model were also commonly fabricated by direct mixing or in situ formation for high-performance or multifunctional devices, such as SnS/SiO x core/shell nanowires, [155] SnS/C nanofiber composites, [30,144] SnS-Sn/CNT composites, [156] etc. For example, in 2020, Yang et al [155] reported well-defined SnS/SiO x core/shell nanowires fabricated by a CVD method using SnS powder as the source.…”
Section: Encapsulated Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It was verified that the as-prepared SnS/C composite microspheres also displayed superior reversible capacities and excellent cycle performance, which have great potential for Na-ion batteries as anode materials. [154] Apart from that, SnS-based nanostructures containing 1D SnS nanomaterials in a capsulated model were also commonly fabricated by direct mixing or in situ formation for high-performance or multifunctional devices, such as SnS/SiO x core/shell nanowires, [155] SnS/C nanofiber composites, [30,144] SnS-Sn/CNT composites, [156] etc. For example, in 2020, Yang et al [155] reported well-defined SnS/SiO x core/shell nanowires fabricated by a CVD method using SnS powder as the source.…”
Section: Encapsulated Modelmentioning
confidence: 99%
“…With respect to the electrochemical performances in batteries, although pure SnS nanostructures, such as 0D SnS NPs, [31] 1D SnS nanostructures, [62,66] 2D SnS NSs or nanoplates, [153,184,185] 3D SnS nanoflowers or yolk-shell microstructures, [32,99,186] have made considerable progress in the field of batteries, such as Li or Na-ion batteries and Li-S batteries, yet its low electronic conductivity, large volume expansion and poor cycling stability during charging and discharging, greatly limit its practical applications. To this end, a number of researches has focused on the functionalization of SnS with graphene, [69,101,124,137,158,159] CNTs, [111,112,156,187] C fibers, [28,30,146] conductive polymers, [138] MoS 2 NSs, [116,147,150] etc., to achieve outstanding electrochemical performances. For example, in 2020, 2D SnS nanoplates modified with abundant S vacancies were synthesized by a self-template strategy for Li-ion batteries as advanced anode materials.…”
Section: Batteries and Solar Cellsmentioning
confidence: 99%
“…High efficiency, clean energy and related advanced technologies have been put forward higher requirements for energy storage device (EES). [1,2] Supercapacitors (SCs) has attracted much attention due to its high-power density, ultra-long cycle life and reliable security. However, the relatively low energy density of SCs compared with that of lithium-ion batteries and fuel cells has hindered its further application.…”
Section: Introductionmentioning
confidence: 99%